Computed tomography has improved precision for prediction of intramuscular fat percent in the M. longissimus thoracis et lumborum in cattle compared to manual grading. (November 2018) - Anderson, F.; Cook, J.; Williams, A.; Gardner, G.E.
Abstract: This study assessed the ability of computed tomography (CT) to predict intramuscular fat (IMF) % in the M. longissimus thoracis et lumborum of 64 cattle undergoing Meat Standards Australia (MSA) marbling score. The striploin was dissected from carcasses at the 12th rib and CT scanned, with IMF% determined at the 12th rib of the M. longissimus thoracis (LT) and the caudal M. longissimus lumborum (LL). Prediction of IMF% using CT in the LT was moderate (R 2 = 0.89, RMSE = 1.91) utilising CT pixel density and standard deviation, and better than prediction using MSA marbling score (R 2 = 0.81, RMSE = 2.47). Prediction of IMF% in the caudal aspect of the LL was comparatively poor (R 2 = 0.63, RMSE = 4.69), with IMF% 1.97% higher in this region ( P < .05). CT is a promising non-destructive method for determination of IMF% that was more accurate than MSA marbling score. Highlights: Computed tomography is more precise than MSA marbling score when predicting IMF % CT can predict IMF% in the M. longissimus thoracis et lumborum of beef with moderate precision IMF% prediction is more precise at the 12th rib of the M. longissimus thoracis than caudal M. longissimus lumborum